Effects of a school-based drug use prevention programme for middle-school students in Taiwan. (February 2015) - Chang, Fong-Ching; Chang, Yu-Chen; Lee, Ching-Mei; Lung, Chih-Ning; Liao, Hsin-Jung; Lee, Shu-Ching; Miao, Nae-Fang; Lin, Sieh-Hwa; Zeng, Wang-Ting
Abstract This study examined the effects of a school-based drug use prevention programme for middle-school students in Taiwan. The curriculum consisted of 10 lessons and 4 homework assignments involving parent–child activities. A quasi-experimental design was used. The study was conducted in an urban middle-school located in Taipei city and in a middle-school located in a rural area in Taoyuan county. A total of 327 middle-school students in the intervention group and 314 students in the comparison group successfully participated in the baseline (September 2011) and follow-up surveys (November 2011). A mixed-model approach was used to examine the effects. Multivariate analysis results indicated that the school-based drug-prevention programme increased the students' drug-related knowledge, drug-prevention attitudes, enhanced life skills, and improved perceived parental involvement in the prevention of drug use. The results of this study endorse the implementation of school-based drug use prevention programmes that include parent–child activities to enhance youth drug-prevention knowledge, attitudes, and life skills.